Using Enterprise Models to Explain and Discuss Autopoiesis and Homeostasis in Socio-technical Systems - Bider, Ilia; Regev, Gil; Perjons, Erik (Complex Systems Informatics and Modeling Quarterly, 2020)
The article links two seemingly different fundamental theoretical concepts of autopoiesis and homeostasis and tries to apply them to the realm of socio-technical systems with the use of the Fractal Enterprise Model (FEM). Autopoiesis is the property of a system that constantly reproduces itself. Homeostasis describes a way a complex system constantly maintains its identity while adapting to changes in its internal and external environment. To be able to use FEM for this task, the original version of FEM has been extended by adding special elements for representing the system's context – part of the environment to which the system is structurally coupled. The approach taken in this article differs from other works in the same field in having the focus on the “body” (concrete elements being reproduced) of the socio-technical system, as well as on identifying concrete processes that reproduce the system, and demonstrating concrete ways of how a specific system adapts or can adapt to the perturbations in the environment (i.e. internal and external disturbances that affect the system).